KONSEP 'AWALIM 'ABD ALLAH BIN 'ABD AL-QAHHAR AL-BANTANI DALAM DISKURSUS WUJUDIYYAH DI NUSANTARA - KURNIAWAN, ADE FAKIH (ALQALAM, 2011)
This article aims at observing the Wujudiyyah teaching of 'Abd Allah bin 'Abd al-Qahhar al-Bantani on the text Masyahid an-Ndik fi maqamat as-Salik. Even though 'Abd Allah bin 'Abd alQahhar al-Bantani was as a great ulama in the period of Sultan Abu an-Nasr 'Arif Syifa' Zain al 'Asyiqin—the ruler of the sultanate of Banten in the eighteenth century--his name was scarcely mentioned in the history of Banten. This sultan asked him to write a book of Wujudiyyah, especially dealing with tajalliyat. The polemic of WuJudiyyah happens in Banten is different from that of in Aceh. In Banten, there is no information stating that the sultan of Banten bans and considers the adherents of wujudiyyah teaching as infidel (unbeliever). Dealing with tajalliyat concept, he expresses it in the explanation of tajalli phases of God over the realm that he divides into four kinds of world: 'alam ilahi, 'alam jabarut, 'alam malakut and 'alam nasut. His division of these worlds is much different from al-Burhanpuri's concept of Martabat Tujuh and the world concepts of Hamzah Fansuri, al-jili as well as lbn 'Arabi. Keywords: WuJudiyyah, 'Awalim, Martabat Tujuh, Maratib Al-Wujud